A Predıctıve Model of Learnıng Independence: Integratıon of Socıal Platform and Self-Regulatıon in College Students - Vera Septi Andrini; Erdyna Dwi Etika; Umi Hidayati (Proceeding International Conference on Digital Education and Social Science, 2024)
In modern research in education, learning independence plays a very important role, especially in the digital era where flexibility implies alignment of endurance. Although most universities in Indonesia use online learning, the consequences of this in the form of academic independence are still unknown. This study intended to model learning independence built with online learning and self-regulation in University of PGRI Mpu Sindok students. The study was conducted among 120 students divided into high and low groups using a quasi-experimental design with group randomization. The multiple linear regression analysis result was the model Y = 0.4923 + 0.6745X1 + 0.2289X2, where Y signifies learning independence, X1 signifies the Intuitiveness of using social learning platforms, and X2 signifies self-regulation. Overall, the model provided significant results p < 0.0001 and explained 50.27% of students' learning independence variation. There is an absence in the impact of using X2 self-regulation simultaneously as using X1 self-regulation. This empiricism concentrates on creating experimental strategies that use self-regulation with technological and educational tools in order to increase students' academic independence-validated in line with the digital era.